2017
DOI: 10.1557/adv.2018.2
|View full text |Cite
|
Sign up to set email alerts
|

Tribological improvement of hardened and tempered AISI 4140 steel against Al2O3 by using bio-lubricant

Abstract: AISI 4140 steel is a popular low alloy steel due to its wide applications as workpiece in the metal-mechanic industry; there are extensive research about surface modification to enhance its properties for specific applications. The focus of this study was to investigate the influence of the nature of lubricants, mineral and vegetable oils, on the tribological performance of the hardened and tempered AISI 4140 steel against alumina (Al2O3). For this purpose, friction tests were conducted in a pin on disc tribom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…For this study, disks of AISI 4140 steel of 5 mm of thickness and 25.4 mm diameter were obtained from a commercial AISI 4140 annealed steel bar. The chemical composition of the steel [9] is: Cr (1.04 wt %), Mn (0.96 wt %), C (0.43 wt %), Si (0.18 wt %), Mo (0.16 wt %), S (0.04 wt %), P (0.03 wt %), and Fe (balance). The optical micrograph in Figure 1 confirmed the steel condition, showing that the microstructure consists of ferrite and coarse pearlite phases.…”
Section: Tribological Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…For this study, disks of AISI 4140 steel of 5 mm of thickness and 25.4 mm diameter were obtained from a commercial AISI 4140 annealed steel bar. The chemical composition of the steel [9] is: Cr (1.04 wt %), Mn (0.96 wt %), C (0.43 wt %), Si (0.18 wt %), Mo (0.16 wt %), S (0.04 wt %), P (0.03 wt %), and Fe (balance). The optical micrograph in Figure 1 confirmed the steel condition, showing that the microstructure consists of ferrite and coarse pearlite phases.…”
Section: Tribological Assessmentmentioning
confidence: 99%
“…In addition to these applications, Madankar et al [8] suggested that Castor oil is a promising bio-lubricant thanks to its good lubricity properties, high viscosity, low pour point, and the low cost of production. In fact, its use has been reported as a bio-lubricant in different studies of its tribological behavior; by comparing it with commercial oils, Castor oil showed significant lubricating effects [5,8,9]. Recently, our research group reported an improvement on the tribological behavior of hardened AISI 4140 steel by using castor oil as bio-lubricant, observing low friction coefficients of up to 0.035, and wear rate values of 1.02 × 10 −8 mm 3 /Nm in a system of 4140/Al 2 O 3 at room temperature [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Green lubricants exhibit low toxicity, excellent biodegradability, and, usually, they are derived from natural vegetable oils [2,5]. The most commonly employed natural oils for producing bio-based lubricants are rapeseed, sunflower, canola, soybean, palm, coconut, and castor oil, to name a few [1,2,[5][6][7][8]. Generally, vegetable oils have excellent lubricating properties, and they also present high viscosity indexes (VI) and high flash points [2,5,8].…”
Section: Introductionmentioning
confidence: 99%